Effizienzgewinn oder staatlicher Kontrollverlust? Privatisierung öffentlicher Verkehrsunternehmen: Erfahrungen aus Sachsen. - Sturm, Sebastian; West, Alexander (Deutscher Verkehrs-Verl., 2007)
Am Beispiel der Privatisierung von Busunternehmen in Ostsachsen wurde nicht nur die Auswirkung der Privatisierung auf eine mögliche Reduktion des Defizits untersucht, sondern auch die Frage nach den Auswirkungen auf die Angebotsqualität analysiert. Dabei stand die Frage im Vordergrund, ob - ausgehend von der Problematik unvollständiger Verträge - eine Beteiligung des Aufgabenträgers am Unternehmen geboten ist, um langfristig die Angebotsqualität abzusichern. difu

Decreasing subsidies for public transport services constrict districts (Landkreise) and municipalities to search for economically more effective solutions. Selling the own public transport company to a private investor and organising the provision of the transport service by a contract could be an opportunity for reducing the need of financial support. Public authorities often chose partial privatisation of their public transport company and continue holding shares in the company. The article analyses the effect of (partial) privatisation on subsidies and quality. Departing from theory of incomplete contracts case studies are used to assess if the privatisation leads to lower subsidies and if the participation of the district / municipality is necessary to ensure the fulfilment of quality standards. It turns out that the privatisation of public transport companies leads to lower costs without reducing service quality. difu
Keywords: Öffentlicher Verkehr; Privatisierung; Busverkehr; ÖPNV; Regionalverkehr; Verkehrsunternehmen; Verkehrsangebot; Erfahrungsbericht